2015
DOI: 10.1152/ajpheart.00721.2014
|View full text |Cite
|
Sign up to set email alerts
|

Depressor effect of chymase inhibitor in mice with high salt-induced moderate hypertension

Abstract: Devarajan S, Yahiro E, Uehara Y, Habe S, Nishiyama A, Miura S, Saku K, Urata H. Depressor effect of chymase inhibitor in mice with high salt-induced moderate hypertension. Am J Physiol Heart Circ Physiol 309: H1987-H1996, 2015. First published October 2, 2015; doi:10.1152/ajpheart.00721.2014.-The aim of the present study was to determine whether long-term high salt intake in the drinking water induces hypertension in wild-type (WT) mice and whether a chymase inhibitor or other antihypertensive drugs could reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
4
18
1
Order By: Relevance
“…Therefore, we examined the effects of a chymase inhibitor in salt-treated animals. These data are in agreement with previous studies that showed chymase-dependent Ang II generation is associated with the development of hypertension in salt-treated mice (Devarajan et al, 2015). These data are in agreement with previous studies that showed chymase-dependent Ang II generation is associated with the development of hypertension in salt-treated mice (Devarajan et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we examined the effects of a chymase inhibitor in salt-treated animals. These data are in agreement with previous studies that showed chymase-dependent Ang II generation is associated with the development of hypertension in salt-treated mice (Devarajan et al, 2015). These data are in agreement with previous studies that showed chymase-dependent Ang II generation is associated with the development of hypertension in salt-treated mice (Devarajan et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that salt-induced moderate hypertension was dose-dependently attenuated by a chymase inhibitor in mice (Devarajan et al, 2015). Previous studies have shown that salt-induced moderate hypertension was dose-dependently attenuated by a chymase inhibitor in mice (Devarajan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been shown that high salt containing water (2% NaCl) intake induced significant elevation of BP and HR two weeks after loading in C57BL/6 male mice 10) . In the present study, when we adopted the high salt water loading (2% NaCl) intervention to our EC-specific heterozygous Dicer KO mice, we did not observe any changes in the hemodynamic parameters of WT C57BL/6 and ECspecific heterozygous Dicer KO female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice were used for all experiments. In high salt loading experiments, mice were given salt water containing 2% NaCl or normal water 10) . The animal protocols were approved by the Animal Care and Use Committee of the University of Tokyo (P14-047) and Waseda University (2017-A103a).…”
Section: Methodsmentioning
confidence: 99%